Synergistic Effects of Ocean Warming and Cyanide Poisoning in an Ornamental Tropical Reef Fish - Madeira, Diana; Andrade, Joana; Leal, Miguel C.; Ferreira, Violeta; Rocha, Rui J. M.; Rosa, Rui; Calado, Ricardo (Frontiers in Marine Science, 2020)
An array of anthropogenic pressures is affecting tropical ecosystems, posing major conservation challenges for scientists, stakeholders and populations. Illegal cyanide fishing is one of the major threats to Indo-Pacific coral reefs, targeting a multitude of colorful species for the marine aquarium trade as well as large-sized groupers and wrasses for the food fish trade. Ultimately, the continued use of this destructive practice as oceans warm may overload tropical ecosystems and result in irreversible ecological damage. Here we show that the impact of cyanide poisoning in ornamental tropical marine fish is magnified under increased temperatures. A sole pulse exposure of 60 seconds to 50 mg L-1 of cyanide under current temperature (26 ºC) caused substantial mortality (50-100 %) in eight species of Pomacentridae. The clownfish Amphiprion ocellaris was the most resilient, especially medium-sized fish (average total length and weight of 38 mm and 1.12 g; LC50 (95% CI) = 50.00 (46.76 – 53.24) mg L-1) that showed shorter recovery times and higher survival rates (%) when compared to small-sized ones (average total length and weight of 25 mm and 0.30 g; LC50 (95% CI) = 28.45 (20.17 – 36.72) mg L-1). However, when the most resistant size-class was concomitantly exposed to a sub-lethal dosage of cyanide (25 mg L-1 instead of 50 mg L-1) and ocean warming scenarios for 2100 (+3 ºC and heat wave +6 ºC), survival rates (%) decreased to 60 % and 20 %, respectively and recovery times increased in the worst case scenario. Mortality outbreaks, as well as vulnerability to predation, will likely expand in fish inhabiting coral reefs exposed to cyanide fishing unless stronger conservation measures are taken in tropical reefs to limit this destructive practice now and in the oceans of tomorrow.